(3TQM GdeSGFd GdUZjQ dMfjf Hf ESMGbs - (3CHh GdbGSe , YHO GdQMef Hf Ydj Hf CMeO Hf CHi UGOb GdfjSCHhQis; (3GHf CHj UGOb , YHO GdQMef Hf Ydj Hf CMeO Hf CHj UGOb, CHh GdbGSe (B- (3HbQGW GdKGfj GdfjSCHhQj,J (B470 (3g` ? s ((3eMeO Hf YHO Gdedc Hf YSGcQ GdTGaYi GdHYdHci s)
(3ChdgG (B:s
(3eHJhQ GdChd ,hjHOC GdTQM GdeNJdag , EdG Cf GdeGOI Ef cGfJ eMehOg YedJ GdbhI s
(3BNQgG (B:s
(3hEPG fYQH (B((3?(B) (3JZjQJ , agi EPf JOd YdjgG HeTGQcI GdYQhb ced s
(3ced TQM GdeSGFd GdUZjQ dCHf CHj UGObs
(3hfbdJ Yf fSNI YJjbI LOkGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdWHs